Contemporary Islamic economic studies on Maqasid Shari'ah: a systematic literature review. Issue 3 (14th August 2017) - Shinkafi, Akilu Aliyu; Ali, Nor Aini
Abstract : Purpose: The purpose of this paper is to come-up with a systematic exertion on Maqasid Shari'ah in Islamic economics, banking and finance, with a clear focus on forming an appropriate and novel framework that identifies the effort of contemporary scholars and detects the existing gap that might possibly champion new research commitments. Design/methodology/approach: A systematic approach to literature review was steered through the means propagated by the Centre for Reviews and Disseminations (DSR), but modified to the precise requirements of this review. Google Scholar was searched throughout the passage. The search criteria are confined to English documents that are within the period of 2006-2016. Articles that did not score or did not convince that the subject of Maqasid Shari'ah has been applied in Islamic economy, Islamic banking, Islamic finance, Islamic financing products and economic development are excluded. Appropriate search keys are used to gather better results. Findings: The findings inform that contemporary scholars show a robust commitment to the themes of the result during the stated period. The outcome reveals that contemporary scholars designate more interest and attention on Islamic banking and expose their potential specialty in the expanse than other themes. The study further highlighted the gap of some significant areas that are either outside the coverage of the reviewed documents or require more attention from contemporary scholars, for instance, wealth formation and management, wealth consumption, socioeconomic security, risk management, corporate governance, management policy, human resource development, prohibition of Riba, profit and loss sharing (PLS), etc. Research limitations/implications: The paper is limited to contemporary aspects of Islamic economics, banking, finance and economic development that have a link with the subject of Maqasid Shari'ah . Practical implications: A review of these scholarly reported documents has the potential to draw attention toward filling the existing gap that will likely result in salvation of current issues on the subject of Maqasid Shari'ah that has a direct association with Islamic economy, banking and finance. Originality/value: The paper is original in its nature considering the fact that it is assumed as the maiden attempt of its kind in the field. It is a treasure to all those who may cherish and find it relevant in their progressive and rounded convention or application on the matter.